Liver Transplantation for the Treatment of Complicated Iatrogenic Biliary Injuries: A National Review from the UNOS Data Set. Issue 12 (December 2017) - Garcia, Catherine R.; Acosta, Luis F.; Mei, Xiaonan; Berger, Jonathan; Shah, Malay B.; Daily, Michael F.; Grigorian, Alla; Gedaly, Roberto
Abstract : Background: Liver transplantation (LT) is rarely indicated in the management of iatrogenic bile duct injuries (IBDI), but occasionally, it becomes the only remaining therapy. The purpose of this study is to evaluate potential complications of IBDI and their impact on perioperative mortality, graft, and patient survival after LT. Methods: The United Network for Organ Sharing database was queried for all LT performed in the United States between 1994 and 2014. Of the 101 238 liver transplants performed, 61 were related to IBDI. We performed a case matched analysis in a 5:1 ratio. Results: The median age for patients with IBDI was 50.16 ± 11.7 years with a mean Model End-Stage Liver Disease score of 22.6 ± 9.8. Patients receiving LT for IBDI were more likely women (54.1%, P = 0.001), had lower incidence of hepatitis C virus infection (4.9%, P = 0.001) and longer cold ischemic time ( P = 0.001). The mean body mass index was 25.5 ± 5.2 in patients transplanted for IBDI. IBDI was recognized as the strongest independent predictor associated with eightfold increased risk of early graft loss ( P = 0.001; odds ratio, 8.4) and a 2.9-fold increased risk of 30-day mortality after LT in a case matched analysis ( P = 0.03). Conclusions: IBDI is an uncommon but challenging indication for LT. These patients have significantly increased rates of early graft loss. IBDI is an independent factor related to increased risk of perioperative death after LT. Further studies are needed to determine the causes of perioperative complications and identify potential modifiable factors to improve outcomes in patients undergoing transplantation for IBDI. Abstract : The authors have examined the little studied clinical experience of liver transplantation for biliary tract injuries. Sixty-one cases have been identified from the entire UNOS experience. Detailed study of these subjects compared to case-matched OLT reveal higher complexity and failure rates.